Peter Drucker and management - Linkletter, Karen E. (Routledge, 2024)
"Peter Drucker is arguable the world's most influential management writer, but his contributions as a social theorist and philosopher are also notable. This book presents Drucker as a key thinker, whose work encompasses ideas about management practice, technology, social developments and trends, the nature of human beings, matters of theology, and, most of all, how to avoid extremes. By positioning Drucker in a wider context, this book is valuable reading for scholar, students and reflective practitioners of management as well as those with an interest in intellectual history more broadly"-- Provided by publisher.
Keywords: Drucker, Peter F. -- (Peter Ferdinand), -- 1909-2005.; Management.; elektronické knihy; electronic books